ATMPH 2020
DOI: 10.36295/asro.2020.232239
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Scavenging Activity of Rosemary Extract and its Activity Against Some Pathogenic Microorganisms

Abstract: Rosemary (Rosmarinus officinalis L.) is one of the most economically important species of the family Lamiaceae. Rosemary extract was examined by applying 2.2-diphenyl-1picrylhydrazyl (DPPH) radical-scavenging assays. The result proved that rosemary extract had a higher antioxidant activity by absorption at a wavelength of 517a nm by using three different concentrations (0.5, 1.0 and 3) mg/ml which performed the absorbance at (2. 314, 0. 211 and 0.296) nm in comparison with control (21.8, 92.2 and 90) nm respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In our study, the rosemary extract was drastic against E. coli , S. typhimurium , A. niger , and Adenovirus. The rosemary extracts were potent against Gram-positive and Gram-negative bacteria in a study by Mahmood et al [ 56 ]. In our experiment, rosemary extract displayed antifungal action against A. niger at concentrations ranging from 25 to 90%, which is consistent with the findings of Swari et al [ 57 ], who demonstrated that rosemary ethanol extract had an inhibitory effect against Candida albicans .…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the rosemary extract was drastic against E. coli , S. typhimurium , A. niger , and Adenovirus. The rosemary extracts were potent against Gram-positive and Gram-negative bacteria in a study by Mahmood et al [ 56 ]. In our experiment, rosemary extract displayed antifungal action against A. niger at concentrations ranging from 25 to 90%, which is consistent with the findings of Swari et al [ 57 ], who demonstrated that rosemary ethanol extract had an inhibitory effect against Candida albicans .…”
Section: Resultsmentioning
confidence: 99%